Defense Against the Black Arts : How Hackers Do What They Do and How to Protect Against It. - Varsalone, Jesse; McFadden, Matthew (Milton : Taylor & Francis Group, 2011)
Exposing hacker methodology with concrete examples, this volume shows readers how to outwit computer predators. With screenshots and step by step instructions, the book discusses how to get into a Windows operating system without a username or password and how to hide an IP address to avoid detection.
FileVault -- FileVault Security Concerns -- TrueCrypt -- iPhone -- Summary -- 14 Wireless Hacking -- Introduction -- Wi-Fi Hardware and Software -- BackTrack Setup: Quick and Dirty -- Monitor Mode -- Cracking WPA-PSK -- Wired Equivalent Privacy Cracking -- Wi-Fi Monitoring and Capturing -- Physical Wi-Fi Device Identification -- WPA Rainbow Tables -- Analyzing Wi-Fi Network Traffic -- Network Analysis -- Example Scenario: "Man in the Middle" -- Summary -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books